PUBLIC RELATIONS (PR) DAN KESALAHPAHAMAN PUBLIK ATAS PEMAKNAAN SEBUAH PROFESI - Prida A.A.A, Prida A.A.A (Institute of Research and Community Outreach - Petra Christian University, 2007)
Practice of public relations have recently led to negative concepts and tended to blur the original concept launched by PR founders. But actually the case is PR is about reputation, taking form of a number of images given to organizations by its public. Image itself has a definition as a reflection of organization's reality, a reality that is seen from organizational public standpoint. Therefore, it can be stated that PR is impossible to be a profession that only sells appearance, smiles and accompanies guests, due those are just a few of activities that should be done by PR. If it is only a part of the activities, it is not PR. Essentially the article wanted to discuss about, whether PR would die and new terms spring up that most of them were related to marketing activities? The Writer resolutely say: no! PR would remain to be primary approach to see how to manage relationship between a company and all of interest holders, relation management with various publics that had pertinence to the organization. Meanwhile terms that have sprung up recently, most of have only prioritized on activities in one or several PR publics only. Or emergence of term corporate communication, approach of the new term remain based on PR concept, due to corporate corporation that was carried out by organization kept on being focused on relation management with stakeholders through communication activities.